Effectiveness of rodents as local seed dispersers of Holm oaks. (Oecologia, 2008)
In this study we assessed the effectiveness of rodents as dispersers of Quercus ilex in a patchy landscape in southeastern Spain. We experimentally followed the fates of 3,200 marked and weighed acorns from dispersal through the time of seedling emergence over three years. Rodents handled about 99% of acorns, and dispersed 67% and cached 7.4% of the dispersed acorns. Most caches were recovered and consumed, and only 1.3% of the original experimental acorns were found alive in caches the following spring. Dispersal distances were short (mean = 356.2 cm, median = 157 cm) and strongly right-skewed. Heavier acorns were dispersed further and were more likely to be cached and survive than lighter acorns. All caches were in litter or soil, and each contained a single acorn. Rodents moved acorns nonrandomly, mostly to oaks and pines. Most surviving acorns were either in oaks, a poor microhabitat for oak recruitment, or shrubs, a suitable microhabitat for oak recruitment. Our results suggest that rodents, by burying a relatively high proportion of acorns singly in shrubs and pines, act as moderately effective dispersers of Q. ilex. Nonetheless, this dispersal comes at a very heavy cost.

Irradiance and oak seedling survival and growth in a heterogeneous environment (Forest Ecology and Management, 2007)
The Mediterranean region emerges highly heterogeneous at every spatio-temporal scale. Key species shape a mosaic of patches (landscape units) composed of different microhabitats. Within these ecosystems irradiance appears as one of the most changing factors affecting communities’ dynamic. However, the impact of irradiance on the species performance is still poorly known. In this study, we intended to explore whether irradiance heterogeneity inﬂuences early recruitment. We chose a patchy Mediterranean site. During 2001, 2002 and 2003 we marked naturally Quercus ilex emerged seedlings. We distinguished three landscape units (Q. ilex woodlands, shrublands and afforestations) and six microhabitats (oak, broom, tall shrub, subshrub, pine and open). For each seedling, we measured (1) irradiance as global site factor (GSF); (2) acorn presence; (3) acorn depth; (4) burial layer; (5) distance to the nearest co-speciﬁc adult. As estimates of seedling performance, we measured seedling survival and height. Estimates of seedling performance were higher in 2001 and 2002 than in 2003. Oak or pine microhabitats achieved higher survival rates than brooms or open areas whilst under oaks, brooms or in open areas seedling height was lower than under tall shrubs. Irradiance signiﬁcantly affected seedling survival and growth. The lower the irradiance, the higher the survival. Maximal growth was found at intermediate irradiance, indicating that, in this system, moderate shade is crucial for Q. ilex seedling recruitment. Some microhabitats provide intermediate irradiance that combines positive effects on survival and growth. As a ﬁnal point, dispersers’ activity creates a heterogeneous distribution of acorn deposition ﬁltering out part of the total irradiance present in the study site.

BIGGER IS NOT ALWAYS BETTER: CONFLICTING SELECTIVE PRESSURES ON SEED SIZE IN QUERCUS ILEX (Evolution, 2004)
Abstract Most theoretical treatments of the evolutionary ecology of offspring size assume a simple and direct effect of investment per offspring on offspring fitness. In this paper I experimentally determine the relationship between seed mass and several main fitness components of the oak Quercus ilex, to estimate phenotypic selection acting on seed mass during the early life cycle and to discover any potential selective conflicts occurring between different stages from dispersal to establishment. I found a positive effect of acorn size on most fitness components related to seedling establishment. Large size increased germination rate and seedling survival, accelerated germination timing, and enhanced seedling growth. Nevertheless, there was also a direct negative effect of acorn size on survival to predation, because large acorns were highly preferred by the main postdispersal seed predators at the study site, wild boars and wood mice. Because of the low probability of escape from predation, the fitness of large acorns estimated on this component was significantly lower than the fitness of smaller acorns. Therefore, seed size affected fitness in two different ways, yielding opposing and conflicting selective forces. These findings suggest that the general assumption that offspring fitness is a fixed positive function of seed size needs to be reconsidered for some systems. The existence of conflicting selection might explain the occurrence of an optimal seed size in some plant species without invoking a seed number-size trade-off.